2019
DOI: 10.1037/xhp0000646
|View full text |Cite
|
Sign up to set email alerts
|

Seeing social events: The visual specialization for dyadic human–human interactions.

Abstract: Detection and recognition of social interactions unfolding in the surroundings is as vital as detection and recognition of faces, bodies, and animate entities in general. We have demonstrated that the visual system is particularly sensitive to a configuration with two bodies facing each other as if interacting. In four experiments using backward masking on healthy adults, we investigated the properties of this dyadic visual representation. We measured the inversion effect (IE), the cost on recognition, of seei… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 40 publications
7
42
0
Order By: Relevance
“…Behavioral research suggests that key properties of social interaction, such as action coherence and agent/patient-role information, correlate with visuo-spatial features that are accessed quickly in visual events (Hafri et al, 2013(Hafri et al, , 2018Glanemann et al, 2016). Moreover, multiple bodies in configurations that imply interaction (e.g., face-to-face), are detected, recognized, and remembered better than unrelated bodies (Ding et al, 2017;Papeo and Abassi, 2019;Vestner et al, 2019).…”
Section: Significance Statementmentioning
confidence: 99%
“…Behavioral research suggests that key properties of social interaction, such as action coherence and agent/patient-role information, correlate with visuo-spatial features that are accessed quickly in visual events (Hafri et al, 2013(Hafri et al, , 2018Glanemann et al, 2016). Moreover, multiple bodies in configurations that imply interaction (e.g., face-to-face), are detected, recognized, and remembered better than unrelated bodies (Ding et al, 2017;Papeo and Abassi, 2019;Vestner et al, 2019).…”
Section: Significance Statementmentioning
confidence: 99%
“…This methodological choice allowed testing the specific hypothesis behind the study, according to which visual perception areas encode for visuo-spatial cues associated with social interaction (i.e., spatial proximity, body orientation and approaching behaviour), rather than the social interaction itself. Based on the above results (Papeo et al 2017a;Papeo and Abassi 2019;Vestner et al 2019; Abassi and Papeo 2020), we expected to find an advantage in processing facing dyads, which we sought to capture in the neural activity (through univariate and multivariate analyses of the fMRI signal, Study 1), as well as in the participants' performance in visual recognition of multiple-body scenarios (Study 2).…”
Section: Introductionmentioning
confidence: 99%
“…Papeo et al [7] found that this perceptual grouping effect (a greater inversion effect for engaged dyads than disengaged) persisted when the heads of the dyads were blurred. More recently Papeo and Abassi [16] showed that blurring the head of bodies does not affect the signature of the dyadic inversion effect. Thus, there is evidence that head orientation is not necessary in eliciting the dyad inversion effect.…”
Section: Introductionmentioning
confidence: 99%